Structure-Dependent Biodistribution of Liposomal Spherical Nucleic Acids - Ferrer, Jennifer R. (ACS Nano, 2020)
Spherical nucleic acids (SNAs) are a class of nanomaterials with a structure defined by a radial distribution of densely packed, short DNA or RNA sequences around a nanoparticle core. This structure allows SNAs to rapidly enter mammalian cells, protects the displayed oligonucleotides from nuclease degradation, and enables co-delivery of other drug cargoes. Here, we investigate the biodistribution of liposomal spherical nucleic acid (LSNA) conjugates, SNA architectures formed from liposome templates and DNA modified with hydrophobic end groups (tails). We compared linear DNA with two types of LSNAs that differ only by the affinity of the modified DNA sequence for the liposome template. We use single-stranded DNA (ssDNA) terminated with either a low-affinity cholesterol tail (CHOL-LSNA) or a high-affinity diacylglycerol lipid tail (DPPE-LSNA). Both LSNA formulations, independent of DNA conjugation, reduce the inflammatory cytokine response to intravenously administered DNA. The difference in the affinity for the liposome template significantly affects DNA biodistribution. DNA from CHOL-LSNAs accumulates in greater amounts in the lungs than DNA from DPPE-LSNAs. In contrast, DNA from DPPE-LSNAs exhibits greater accumulation in the kidneys. Flow cytometry and fluorescence microscopy of tissue sections indicate that different cell populations—immune and nonimmune—sequester the DNA depending upon the chemical makeup of the LSNA. Taken together, these data suggest that the chemical structure of the LSNAs represents an opportunity to direct the of nucleic acids to major tissues outside of the liver.